A Large Sample of Extremely Metal-poor Galaxies at z < 1 Identified from the DESI Early Data - Hu Zou; Jipeng Sui; Amélie Saintonge; Dirk Scholte; John Moustakas; Malgorzata Siudek; Arjun Dey; Stephanie Juneau; Weijian Guo; Rebecca Canning; J. Aguilar; S. Ahlen; et al. (The Astrophysical Journal, 2024)
Extremely metal-poor galaxies (XMPGs) at relatively low redshift are excellent laboratories for studying galaxy formation and evolution in the early universe. Much effort has been spent on identifying them from large-scale spectroscopic surveys or spectroscopic follow-up observations. Previous work has identified a few hundred XMPGs. In this work, we obtain a large sample of 223 XMPGs at z < 1 from the early data of the Dark Energy Spectroscopic Instrument (DESI). The oxygen abundance is determined using the direct T _e method based on the detection of the [O iii ] λ 4363 line. The sample includes 95 confirmed XMPGs based on the oxygen abundance uncertainty; the remaining 128 galaxies are regarded as XMPG candidates. These XMPGs are only 0.01% of the total DESI observed galaxies. Their coordinates and other properties are provided in the paper. The most XMPGs have an oxygen abundance of ∼1/34 Z _⊙ , a stellar mass of about 1.5 × 10 ^7 M _⊙, and a star formation rate of 0.22 M _⊙ yr ^−1 . The two most XMPGs present distinct morphologies suggesting different formation mechanisms. The local environmental investigation shows that XMPGs preferentially reside in relatively low-density regions. Many of them fall below the stellar mass–metallicity relations (MZRs) of normal star-forming galaxies. From a comparison of the MZR with theoretical simulations, it appears that XMPGs are good analogs to high-redshift star-forming galaxies. The nature of these XMPG populations will be further investigated in detail with larger and more complete samples from the ongoing DESI survey.